Rhizogenic agrobacteria in hydroponic crops: epidemics, diagnostics and control. (19th March 2017) - Bosmans, L.; Moerkens, R.; Wittemans, L.; De Mot, R.; Rediers, H.; Lievens, B.
Abstract : Rhizogenic Agrobacterium biovar 1, harbouring an Ri‐plasmid (root‐inducing plasmid), is the causative agent of hairy root disease (HRD) in the hydroponic cultivation of tomato, cucumber and aubergine. The disease is characterized by extensive root proliferation leading to strong vegetative growth and, in severe cases, substantial losses in marketable yield. Agrobacterium biovar 1 is a heterogeneous group of agrobacteria and includes at least 10 genomospecies, among which at least four (G1, G3, G8 and G9) have been associated with HRD in hydroponically grown vegetables. This review has synthesized the current knowledge on rhizogenic Agrobacterium biovar 1, including infection process, current taxonomic status, genetic and phenotypic diversity, detection methods and strategies for disease control. With regard to the latter, symptom reduction and prevention of infection through cultivation methods and chemical disinfection (e.g. by the use of chlorine‐based disinfectants and hydrogen peroxide) are discussed and biocontrol strategies are elaborated on. Recent research has led to the identification of a phylogenetically related clade of Paenibacillus strains that have antagonistic activity against rhizogenic Agrobacterium biovar 1 strains, holding great potential for HRD control. Finally, possible directions for future research are proposed.